TINJAUAN MENGENAI SISTEM INFORMASI DAN KEAMANAN INFORMASI PADA PT TRINUSA TRAVELINDO - Edy Soesanto; Vina Damayanti; Indra Samuel; Harfanly Bramley (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Threats to critical asset and file security are increasing rapidly. Cybercriminals are getting smarter and more adept at using the security vulnerabilities of digital systems. To improve cybersecurity, a thorough analysis of the threats faced in the digital environment and practical solutions are required. On this occasion, the author will talk about the implementation of information systems at PT Trinusa Travelindo, also known as Traveloka. Traveloka offers Indonesians a wide range of online services, including airline and hotel bookings, as well as expansion into trains, buses, car rentals, and tourist activities. It is interesting to talk about how Traveloka applies information systems to its business until it becomes one of the Unicorns in Indonesia. The purpose of this research is to analyze important items, find the main problems in protecting it from cyber attacks, assess and suggest methods and strategies to improve file security, and conduct case studies on threats and solutions for the digital world. qualitative approach that uses literature study. Hacking, cracking, cyber sabotage, and spyware are some of the potential cybercrime threats in Indonesia. Identification, assessment, handling, and risk control are all part of the risk management process. To prevent these threats, technology experts are needed to help build a more sophisticated national defense system and build a cybersecurity command center.